MINI REVIEW: SINTESIS DAN KARAKTERISASI NANOPARTIKEL ZnO DAN APLIKASINYA SEBAGAI FOTOKATALIS - Setiawan, M. Pratsojo; Hindryawati, Noor; Aziz, Abdul (PROSIDING SEMINAR KIMIA, 2024)
This mini review will explore the multifunctional of ZnO nanomaterials. ZnO The multifunctional ZnO nanomaterial due to its inexpensive nature, eco-friendly, structure-dependent properties, and complete mineralization of pollutants make them more efficient semiconducting photocatalysts than other materials and good UV absorption. ZnO has many applications in everyday life such as for photocatalysts, antibacterials, edible coatings, and others. Based on the literature review, ZnO material can be synthesized using sol-gel, hydrothermal, solvothermal, precipitation and coprecipitation methods. So, this article reviews the recent developments in the degradation of Methylene Blue and Rhodamine B, which are cationic dyes, by examining operational parameters such as reaction time, initial dye concentration, and catalyst concentration. Keywords: Nanoparticles, Nano materials, Photocatalyst.